A Novel Hybrid of Chloroquine and Primaquine Linked by Gold(I): Multitarget and Multiphase Antiplasmodial Agent. (24th November 2020) - de Souza Pereira, Caroline; Costa Quadros, Helenita; Magalhaes Moreira, Diogo Rodrigo; Castro, William; Santos De Deus Da Silva, Romulo Ivisson; Botelho Pereira Soares, Milena; Fontinha, Diana; Prudêncio, Miguel; Schmitz, Vinicius; Dos Santos, Hélio F.; Gendrot, Mathieu; Fonta, Isabelle; et al.
Abstract: Plasmodium parasites kill 435 000 people around the world every year due to unavailable vaccines, a limited arsenal of antimalarial drugs, delayed treatment, and the reduced clinical effectiveness of current practices caused by drug resistance. Therefore, there is an urgent need to discover and develop new antiplasmodial candidates. In this work, we present a novel strategy to develop a multitarget metallic hybrid antimalarial agent with possible dual efficacy in both sexual and asexual erythrocytic stages. A hybrid of antimalarial drugs (chloroquine and primaquine) linked by gold(I) was synthesized and characterized by spectroscopic and analytical techniques. The CQPQ‐gold(I) hybrid molecule affects essential parasite targets, it inhibits β‐hematin formation and interacts moderately with the DNA minor groove. Its interaction with PfTrxR was also examined in computational modeling studies. The CQPQ‐gold(I) hybrid displayed an excellent in vitro antimalarial activity against the blood‐stage of Plasmodium falciparum and liver‐stage of Plasmodium berghei and efficacy in vivo against P. berghei, thereby demonstrating its multiple‐stage antiplasmodial activity. This metallic hybrid is a promising chemotherapeutic agent that could act in the treatment, prevention, and transmission of malaria. Abstract : Three in one : A novel multitarget metallo‐hybrid of chloroquine and primaquine linked by gold(I) with potent antiparasitic activity and selectivity against two different stages of malaria – the blood (asexual) and the liver stage – has been developed. It acts on at least three identified targets of the parasite: it inhibits the β‐hematin formation, interacts with DNA and interacts of PfTrxR.